Incidental finding of bilateral lateral vaginal wall fibroid, in an antenatal patient during course of labor - Prajapati, Pooja; Prajapati, Kirti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Vaginal leiomyomas remain an uncommon entity with only about 300 reported cases since the first detected case back in 1733 by Denys de Leyden. We report a case of 25-year-old G2P1L1 (Previous FTNVD), who presented inpatient department with c/o 10 months amenorrhea with lower abdominal pain for one day. On general physical examination, no pallor, no Jaundice, no edema and vitals were stable. On per abdominal examination 1-2 uterine contraction for 10 second in 10 min was observed. On per vaginal examination internal OS was 2 cm dilated, 20-30% effaced, vertex at-3, medium consistency, mid position, membrane intact and pelvis adequate noted. She was admitted in labor room and kept watched for spontaneous progression of normal labor. After 6 h of admission, she started having adequate uterine contractions 2-3 for 30 sec in 10 min. On PV examination she was 6 cm dilated with 60-70% effaced, vertex at -1, soft consistency, anterior position. Artificial rupture of membrane was done. Liquor was clear. Inj oxytocin in drip was started at 8 drops/min. During vaginal examination, A firm sessile, painless mass with smooth surface of size 1×1 cm was felt on both right and left vaginal wall which suggestive of vaginal leiomyoma grossly. During course of labor, progression of labor was halted during second stage of labor. Inj oxytocin drop rate increased at 32 drops/min to achieve adequate uterine contraction. A male baby of 2.8 kg was delivered in stable condition. Right mediolateral episiotomy was repaired with rapid vicryl suture 2,0. Patient was informed and vaginal fibroid finding was mentioned on discharge summary. Patient was called after 6 weeks for follow-up.